Enhancing Mathematics Education with Geometrix: A Study on the Effectiveness of Gamified 2D and 3D Animation Tools - Leite, Vitor M. A. F.; Duarte, Felipe V.; Freitas, Havillon B.; Pinheiro, Thomaz A. de S.; Marques, Renan X.; Vidal, C. A.; Cavalcante-Neto, J. B. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.242318, 2024)
This paper presents a comprehensive study on integrating computer graphics and virtual reality into the teaching of geometry, with a focus on complex visualization concepts. The authors developed Geometrix, an interactive software leveraging React and WebGL, to create a gamified learning environment to increase student motivation and understanding of mathematical topics. A pilot study involving high school students demonstrated significant improvements in test scores and student preference for the software over traditional teaching methods. The study highlights the potential of visualization tools and gamification techniques in transforming mathematics education, making it more engaging and accessible for students.